2006
DOI: 10.1116/1.2217973
|View full text |Cite
|
Sign up to set email alerts
|

Studies of plasma surface interactions during short time plasma etching of 193 and 248nm photoresist materials

Abstract: As the device dimensions scale to 100nm, the use of photoresist materials is suitable for lithographic patterning at 193nm. The molecular structure of 193nm photoresist materials is significantly different from that of 248nm photoresist materials [H. Ito, IBM J. Res. Deu. 45, 683 (2001), T. Kajita et al., Proc. SPIE 4345, 712 (2001)], which leads to a number of undesirable consequences, including pronounced surface and line edge roughness during plasma etching [H. Ito, IBM J. Res. Deu. 41, 69 (1997), [E. Reich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 25 publications
2
32
0
2
Order By: Relevance
“…But, as reference resist is etched faster, it develops higher roughness for a given processing time. This is consistent with other studies 13,14,35,36 that show that polymers with greater plasma induced material loss present increased surface roughness. The reason is that during steady state etching, the existing surface roughness can be amplified by an ion induced transfer mechanism where locally nonuniform removal rates lead to enhanced surface roughness since low and high surface features will not be etched at the same rate.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…But, as reference resist is etched faster, it develops higher roughness for a given processing time. This is consistent with other studies 13,14,35,36 that show that polymers with greater plasma induced material loss present increased surface roughness. The reason is that during steady state etching, the existing surface roughness can be amplified by an ion induced transfer mechanism where locally nonuniform removal rates lead to enhanced surface roughness since low and high surface features will not be etched at the same rate.…”
Section: Discussionsupporting
confidence: 94%
“…This is consistent with previous works. 3,5,13,14,36 Hua et al 13 observed that rough surfaces develop within few seconds of exposure of 193 nm PR to FC plasma, and that the transfer of surface roughness produces rough sidewalls that exhibit vertical aligned features. Similar observations were made on 248 nm photoresist.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…While studies addressing issues of either photoresist ͑PR͒ materials [1][2][3] or discharge conditions 4,5 on PR degradation have been published, a combined study of both PR material and plasma conditions has been missing.…”
Section: Introductionmentioning
confidence: 99%
“…Since several studies have suggested that the surface roughness of ArF photoresist films is linearly proportional to the LER in patterned ArF photoresist films and the formation mechanisms of surface roughness and LER are identical. [10,11] Therefore, the discussion on surface roughness can also be applied to LER in this paper. Figure 3 shows the etching rate of the ArF photoresist films.…”
Section: Surface Analysismentioning
confidence: 98%